2021
DOI: 10.25078/yb.v4i2.2768
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and Non-Verbal Signs in Facial Wash Advertisements: A Semiotic Analysis

Abstract: This study involves the discovery of verbal and non-verbal signs, which also describe the meaning of verbal and non-verbal signs found in the facial wash commercial advertisements. The data were taken from three printed facial wash advertisements. The data source has been taken from the internet. This study used the semiotic hypothesis provided by Saussure (1983: 65) to find out the verbal and non-verbal signs and the theoretical meaning provided by Barthes (1977) to find out the meaning of verbal and non-verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to Leech (1981), the meaning that is seen or appears in an advertisement is a complex thing including concepts, ideas, creations, and feelings that are combined into one to produce a unique advertisement. Andriani, Pratiwi, & Santika (2021) results of the researchers found 11 verbal signs and 10 visual signs from the 3 advertisements used in face wash. From these findings, more verbal signs were found than nonverbal ones. This indicates that in the advertisement for the face wash, more verbal signs tend to be found.…”
Section: Introductionmentioning
confidence: 94%
“…According to Leech (1981), the meaning that is seen or appears in an advertisement is a complex thing including concepts, ideas, creations, and feelings that are combined into one to produce a unique advertisement. Andriani, Pratiwi, & Santika (2021) results of the researchers found 11 verbal signs and 10 visual signs from the 3 advertisements used in face wash. From these findings, more verbal signs were found than nonverbal ones. This indicates that in the advertisement for the face wash, more verbal signs tend to be found.…”
Section: Introductionmentioning
confidence: 94%
“…This study is study by (Trisnayanti, et al 2021). And analysis of semiotics found in facial wash advertisement that focused on finding the verbal and visual sign and the meaning contained in the advertisement (Andriani, et al 2021). Other latest related research was about discovering the meaning of verbal and visual signs in Loreal Paris advertisements (Andina, et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that there were found 41 verbal signs and 32 non-verbal signs with two research problem which are what verbal and non-verbal sign used in skincare advertisement and what is the meaning of verbal and non-verbal signs in skincare advertisements. The fifth thesis with the tittle "An Analysis of Verbal and Non-verbal Signs in the Selected Facial Wash Advertisement" written by " Andriani (2021). They found that there are 35 verbal and 28 visual sign.…”
Section: Introductionmentioning
confidence: 99%